Allegories of Gender: Transgender Autology versus Transracialism - Dutta, Aniruddha (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
This article explores how race and gender become distinguished from each other in contemporary scholarly and activist debates on the comparison between transracialism and transgender identities. The article argues that transracial-transgender distinctions often reinforce divides between autological (self-determined) and genealogical (inherited) aspects of subjectivity and obscure the constitution of this division through modern technologies of power.